Management situation of lead acid batteries in Peru - Blas Marreros, Santiago (2022)
The present investigation describes the various environmental socioeconomic problems and the risks that threaten health, due to the development of the secondary lead industry in Peru, this situation contrasts the state of the secondary lead industry with developed countries and proposes objectives of alternatives. sustainable for the Peruvian territory. The method used is descriptive and comparative, consisting of the search, evaluation and analysis of the facts. Currently, lead-acid batteries are disposed of in open-air dumps without measures to protect human and environmental health, and legal provisions are also lacking. Batteries contain toxic elements that can increase the levels of air, soil and water pollution in the areas where they are dismantled. It is concluded that lead is recognized as a toxic and dangerous substance. because they generate toxic gases causing damage to man, animals and ecosystems. In Peru, processes are not carried out with the guarantee of engineering controls and it lacks regulations for adequate dispersion and management of internal contaminants in the process (there are no degrees of sanction and responsibilities of those involved such as manufacturers, importers, wholesalers, retailers and others). end users.